Uncovering Gender Dimensions in Antimicrobial Resistance: A 10-Year Study of Clinical Bacterial Isolates in Uganda - Joel Bazira; Nakato Constance Nakimuli; Nalumaga Pauline Petra; Brenda Nakazibwe; Abel W. Walekhwa; Kawuma Simon; Hope Derick; Iramiot Jacob; Lawrence Mugisha (Cureus, 2025)
Background: Antimicrobial resistance (AMR) and multidrug resistance (MDR) are escalating global health threats, particularly in low- and middle-income countries (LMICs). Understanding gender-specific resistance patterns is essential for inclusive antimicrobial stewardship and gender-targeted interventions. Objective: This study aimed to investigate gender-specific trends in AMR and MDR among clinical bacterial isolates collected from Mbarara Regional Referral Hospital, Uganda, within a 10-year period (2014-2024). Methods: A total of 4,170 non-duplicate clinical isolates subjected to antimicrobial susceptibility testing (AST) were retrospectively analyzed. Gender-specific resistance patterns were calculated and compared using the Wilcoxon signed-rank test, Chi-square, and Fisher’s exact test. All analyses were performed in Python (Google Colab). Results: Among all isolates, 92.7% were resistant to at least one antibiotic, while 71.6% were multidrug resistant. While resistance appeared higher in female-submitted isolates in unadjusted analysis, adjusted models showed that urinary AMR was significantly higher among reproductive-age women (OR = 1.38, 95% CI: 1.22-1.57), while non-urine AMR was elevated in male-submitted specimens from children (OR = 1.45, 95% CI: 1.20-1.76) and adults aged ≥50 (OR = 1.36, 95% CI: 1.13-1.63). MDR showed distinct organism gender associations: it was more common in male-associated urinary Enterobacterales (OR = 1.41, 95% CI: 1.10-1.82), in female-linked non-urine Staphylococcus aureus (OR = 1.62, 95% CI: 1.16-2.27), and in male linked Pseudomonas aeruginosa (OR = 1.56, 95% CI: 1.12-2.18). Conclusion: This study reveals distinct gender disparities in AMR and MDR patterns, structured by age, specimen type, and organism. These findings support the integration of gender-sensitive variables such as pregnancy status, contraceptive use, and care-seeking behavior to better explain resistance pathways and support gender-responsive AMR control in LMICs.
Keywords: amr surveillance; antimicrobial resistance; gender disparities; global health; multidrug resistance; uganda.